Correlation Between Hba1c Levels, Emotional Stress And Dm Distress In Type 2 Diabetes Mellitus Patients - Adang Muhammad Gugun; Yusuf Alam Romadhon Suryanto; Muhammad Emil Fadli Nugroho; Pravda Bintang Bari (CV. Inara, 2025)
This study aimed to examine the correlation between HbA1c levels, emotional distress, and diabetes-related distress (DM distress) among patients with type 2 diabetes mellitus (T2DM). Poor diabetes control and life stressors often lead to increased emotional and DM distress, which may elevate blood glucose through activation of the hypothalamic–pituitary–adrenal (HPA) axis. An analytical observational method with a cross-sectional design was used. Participants were outpatients with T2DM at PKU Muhammadiyah Gamping Hospital, selected using purposive sampling based on inclusion and exclusion criteria. HbA1c levels were analyzed using the boronate affinity method. Emotional distress was measured using the Depression Anxiety Stress Scale (DASS-42), and DM distress was assessed using the Diabetes Distress Scale (DDS-17). Statistical analysis employed the Shapiro–Wilk test for normality and the Spearman correlation test, with a significance level of α = 0.05. A total of 45 subjects participated (23 males and 22 females). The mean HbA1c level was 9.2 ± 2.6%, the mean emotional distress score was 80.2 ± 19, and the mean DM distress score was 2.49 ± 0.93. The results revealed significant positive correlations between HbA1c levels and emotional distress (r = 0.46, p = 0.001), HbA1c levels and DM distress (r = 0.52, p = 0.000), and between emotional distress and DM distress (r = 0.62, p = 0.000). These findings indicate that higher emotional and DM distress are associated with poorer glycemic control. Integrating psychosocial evaluation and emotional support into diabetes care is essential to improve metabolic and psychological outcomes in T2DM patients.